Effect of different sulfur-containing compounds on the structure, sensory properties and antioxidant activities of Maillard reaction products obtained from Pleurotus citrinopileatus hydrolysates. (15th December 2022) - Zhang, Weiwei; Han, Yaqian; Shi, Kexin; Wang, Jianming; Yang, Chen; Xu, Xu
Abstract: To convert this underutilized P. citrinopileatus which is well known for its savory taste into the high value-added food ingredients, the influence of different sulfur-containing compounds, including l -cysteine (Cys), l -methionine (Met) and thiamine (Thi) on the structure, sensory profiles and antioxidant activities of Maillard Reaction products (MRPs) obtained from P. citrinopileatus was evaluated and compared. Sulfur-containing substances significantly enhanced the Maillard reaction progress and antioxidant activities of MRPs. Cys-MRPs showed the strongest fluorescence intensity and the lowest particle size. Partial least squares regression (PLSR) analysis showed that thiols and Maillard peptides formed in Cys-MRPs exhibited meat-like aroma, kokumi and umami taste, while Met-MRPs exhibited caramel-like aroma attributed to the formation of furans. Therefore, the improvement of MRPs obtained from P. citrinopileatus with various sulfur-containing substances could increase their industrial potential as flavor enhancers with higher antioxidant activities. Highlights: Effects of sulfur-containing compounds on properties of P. citrinopileatus protein MRPs were evaluated. Cys-MRPs had the strongest fluorescence intensity and the lowest particle size. The balance of sulfur compounds of MRPs dominated the intensity of meaty and Kokumi taste. Cys-MRPs exhibited relatively high antioxidant activity. PCH/xylose/cysteine model system would be a good flavor enhancer precursor.